Corn yield and soil nitrogen following winter annual cover crops interseeded into soybean. Issue 5 (12th July 2020) - Norris, Robert; Chim, Bee Khim; Evanylo, Gregory; Reiter, Mark; Thomason, Wade
Abstract: Nitrogen demand for corn ( Zea mays L.) production is high, and winter annual cover crops (WCC) can be an alternative source of plant‐available N. Common corn–soybean [ Glycine max (L.) Merr.] rotations in the Mid‐Atlantic region leave fields fallow after soybean, providing a niche for WCC. The objective of this research was to evaluate the effect of rye ( Secale cereale L.), hairy vetch ( Vicia villosa Roth subsp. Villosa ), and rye–vetch mixture WCC interseeded into soybean on soil N, corn grain yield, and fertilizer N replacement from cover crops. Eight different field sites were seeded into standing soybeans in Virginia from 2012–2014. The experiment was a split‐plot design with WCC species as the main plot in a full factorial arrangement with N rate (0 or 45 kg N ha −1 as starter fertilization at planting, and sidedress rates of 0, 45, 90, 135, and 180 kg N ha −1 ) as subplots. Maximum corn grain yield following hairy vetch WCC was 0.7 and 0.6 Mg ha −1 higher than when following rye at 0 and 45 kg ha −1 starter N, respectively. At one site where hairy vetch biomass was >2 Mg ha −1, corn grain yield increased beyond levels attributable only to the addition of legume N. Instead of decreasing the sidedress N requirement, optimum N rates with hairy vetch were similar to other WCC, only with higher yields. Hairy vetch WCC generally resulted in higher soil N than other WCC at the V4 stage of corn, but no differences after corn harvest.